PENGARUH KOMPENSASI, SERVANT LEADERSHIP DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI KERTHI SARI JAYA PEDUNGAN DENPASAR - Ni Komang Sasmita Agustini; I Ketut Setia Sapta; I Gede Rihayana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Kerthi Sari Jaya Pedungan Cooperative Denpasar is one of the companies engaged in microfinance. The main basis for cooperative activities is trust, both in terms of raising funds and distributing funds. In the competition between cooperatives in collecting public funds, many efforts have been taken by cooperatives, including promoting types of savings that are equipped with a number of attributes that can stimulate people's interest in saving. The purpose of this study was to determine and analyze the effect of compensation on employee performance at the Kerthi Sari Jaya Pedungan Cooperative, Denpasar. To find out and analyze the influence of servant leadership on employee performance at the Kerthi Sari Jaya Pedungan Cooperative, Denpasar. And to find out and analyze the effect of work discipline on employee performance at the Kerthi Sari Jaya Pedungan Cooperative, Denpasar. Data was collected by distributing questionnaires and the sampling method used was a saturated sample, namely all 35 employees. Testing the research hypothesis using SPSS 25.0 for Windows. The results showed that compensation has a positive and significant effect on employee performance. Servant Leadership has a positive and significant effect on employee performance. And work discipline has a positive and significant effect on employee performance. In the process of this research, there are limitations experienced, namely, in the data collection process, the information provided by respondents through questionnaires sometimes does not show the actual opinion of the respondents.